1984
DOI: 10.1113/jphysiol.1984.sp015247
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology and enkephalin immunoreactivity of identified myenteric plexus neurones of guinea‐pig small intestine.

Abstract: SUMMARY1. Intracellular injection of the fluorescent dye, Lucifer Yellow CH, revealed the shapes of neurones in the myenteric plexus of the guinea-pig ileum, and these shapes were correlated with the electrophysiological properties and enkephalin immunoreactivity of the neurones.2. A total of eighty-three neurones were filled using electrodes containing a 5 % solution of the dye. Forty-six cells had many short processes and a single long process (Dogiel type 1) and twenty-four cells had essentially smooth soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 26 publications
6
59
0
Order By: Relevance
“…Between 10 and 35% of myenteric neurons belong to this group (Furness and Costa, 1987). These neurons have large, smooth cell bodies (Dogiel Type II morphology), are usually located centrally within the ganglia, and often give rise to several long processes (Bomstein et al, 1984a;Erde et al, 1985;Iyer et al, 1988). About 85% of AH neurons are immunoreactive for calcium binding protein (calbindin D 28K) and do not provide terminals to the muscle (Furness et al, 1988a;Iyer et al, 1988).…”
Section: Vesicles In Sp-immunoreactive Nerve Fibersmentioning
confidence: 99%
“…Between 10 and 35% of myenteric neurons belong to this group (Furness and Costa, 1987). These neurons have large, smooth cell bodies (Dogiel Type II morphology), are usually located centrally within the ganglia, and often give rise to several long processes (Bomstein et al, 1984a;Erde et al, 1985;Iyer et al, 1988). About 85% of AH neurons are immunoreactive for calcium binding protein (calbindin D 28K) and do not provide terminals to the muscle (Furness et al, 1988a;Iyer et al, 1988).…”
Section: Vesicles In Sp-immunoreactive Nerve Fibersmentioning
confidence: 99%
“…A variety of characteristics can be used to identify AH cells; chief among them is the long afterhyperpolarization that follows their action potentials (see Wood, 1994, for reviews). Many AH cells have been demonstrated to have Dogiel type II morphological features (Bornstein et al, 1984;Erde et al, 1985;Katayama et al, 1986;Iyer et al, 1988;Hendriks et al, 1990;Bornstein et al, 1991) with large round or oval cell bodies and several long, tapering processes that run circumferentially out of the ganglion of origin and which give rise to varicose endings in surrounding myenteric ganglia (Bornstein et al,199 I ). A subtype of Dogiel type II neuron, with multiple, short dendritic processes, has also been described (Stach, 1989) and shown to have a different pattern of local projections to other Dogiel type II neurons .…”
mentioning
confidence: 99%
“…FURNESS et al (1983 b) demonstrated that a majority of enkephalin neurons in the guinea pig small intestine possessed many short processes and a single long process. BORNSTEIN et al (1984) proposed that enkephalin neurons in the guinea pig ileum were all Dogiel's type 1 cells. On the other hand, we were able to show that there were many unclassifiable enkephalin neurons in the guinea pig duodenum and proximal colon (KoBAYASHI et al, 1984(KoBAYASHI et al, , 1985.…”
Section: Discussionmentioning
confidence: 99%